2013
DOI: 10.1093/ejcts/ezt183
|View full text |Cite
|
Sign up to set email alerts
|

A 17-year experience with mitral valve repair with artificial chordae in infants and children†

Abstract: MV repair with artificial chordae in infants and children is safe and effective and associated with a low reoperation rate. Further investigation into the long-term durability and biological adaptation of ePTFE sutures after patient growth is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
1
14
0
4
Order By: Relevance
“…Minatoya et al reported that ePTFE sutures were covered only with thin layers of endothelial tissue after 7.5 years in a patient, and suture flexibility and pliability were preserved. The durability of artificial chordae has also been demonstrated and confirmed by other studies …”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Minatoya et al reported that ePTFE sutures were covered only with thin layers of endothelial tissue after 7.5 years in a patient, and suture flexibility and pliability were preserved. The durability of artificial chordae has also been demonstrated and confirmed by other studies …”
Section: Methodssupporting
confidence: 80%
“…Lee et al evaluated a cohort of 139 children, 9.6% of whom had artificial chordae implanted, with an overall survival rate of 97% after 15 years. Freedom from a MV reoperation was 92.5% and 90.4% at 5 and 10 years, respectively, with a low incidence of recurrent MR reported in a chordae repair study by Oda et al This technique enabled the surgeon to avoid prosthetic valve replacement in children with mitral disease, which delayed valve replacement.…”
Section: Methodsmentioning
confidence: 92%
“…[ 1 2 ] Since chordal replacement with PTFE suture was introduced, it has been widely adopted and the outcomes are satisfactory. [ 3 4 5 6 7 18 ] However, there are still two major problems affecting the results of artificial chordal technique for treating MR. One is adjusting the accurate length of artificial chordate, and the other is tying the knot at the intended length. At present, several techniques have been described to overcome these two problems.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 2 ] The polytetrafluoroethylene (PTFE) suture has been applied as artificial chordae in large series with good outcomes. [ 3 4 5 6 7 ] However, artificial chordae remains challenging for cardiac surgeon because of the difficulties in adjusting the accurate length of artificial chordae and tying the knot at the intended length. Nowadays, various techniques for making artificial chordae adjustment and tying knot have been reported, but the results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Some report a favorable late outcome that may be attributable to an age-proportional growth of the papillary muscle. 24 For prolapse of the posterior middle scallop, on the other hand, a sliding leaflet technique has been our method of choice. This technique was first reported by Carpentier's group, 25 followed by other variations.…”
Section: Ando M Et Almentioning
confidence: 99%